Estimating forest leaf area index using satellite images: comparison of k-NN based Landsat-NFI LAI with MODIS-RSR based LAI product for Finland - Härkönen, Sanna; Lehtonen, Aleksi; Manninen, Terhikki; Tuominen, Sakari; Peltoniemi, Mikko
2015